Pengembangan Aplikasi Mobile dengan Teknologi Virtual Reality (VR) untuk Meningkatkan Minat Belajar Siswa dalam Mata Pelajaran Bahasa Indonesia di MTs Negeri 12 Kuningan - Aryanto, Aryanto; Zakaria, Yoyo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine the effectiveness of a Virtual Reality (VR)-based mobile application in increasing students' interest and understanding of Indonesian language subjects. The study used a pre-experimental method with a One Group Pretest–Posttest Design. The population was from class VIII A to D with a sample of class VIII B of 29 students selected. Data analysis techniques included normality, homogeneity, paired sample t-test, validity, and reliability tests. The research results indicate a significant improvement in student learning outcomes after the treatment. The average pretest score of the students is 54.14, while the average posttest score increased to 75.52. The normality test shows that the data is normally distributed, the homogeneity test shows homogeneous variance, and the Paired Sample t-Test produces a significance value of 0.001 < 0.05, indicating a significant difference between the pretest and posttest. The validity test shows that most of the items are valid, while the reliability of the instrument has a Cronbach's Alpha value of 0.602, which falls into the reliable category. These findings prove that the use of VR through the VR3D Movies application is effective in increasing students' interest and learning outcomes, as evidenced by the increase in enthusiasm, motivation, and active engagement during learning.